The Effect of Digital Marketing on Interest in Buying Indihome Products with the Role of Brand Image as an Intervening Variable - Victor, Victor; Meitiana, Meitiana; Kristinae, Vivy; Aprilita, Aprilita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the effect of digital marketing on purchase intention of IndiHome products, with brand image as an intervening variable. This study contributes to understanding the effectiveness of digital marketing strategies in increasing customer purchase intention and strengthening brand image. This research uses the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with a quantitative approach. Data were collected through questionnaires distributed to 100 IndiHome customers in Palangka Raya. The results showed that digital marketing has a positive and significant effect on purchase intention, both directly and indirectly through improving brand image. These findings emphasize the importance of an effective digital marketing strategy in shaping brand image and driving customer purchasing decisions. The implications of this research can help PT Telkom in optimizing marketing strategies to increase IndiHome's competitiveness in the telecommunications industry.